Learning with IT: towards a research agenda - questions and issues - Howard , Ursula (Research in Learning Technology)
Rather like the pencil - whose departure was predicted in 1938 by the New York Times in the face of ever more sophisticated typewriters - the fax, the copier and paper documents refuse to be dismissed. People find them useful. Paper has wonderful properties - properties that lie beyond information, helping people work, communicate and think together. Historians have long argued that the story of the industrial revolution cannot be told by looking at the train alone. Historians might as well whistle for all the effect they have had. The myth of the train is far more powerful. Today it’s the myth of information that is overpowering richer explanations (of) the changes society is experiencing. DOI:10.1080/0968776000080305